2018
DOI: 10.1155/2018/7850671
|View full text |Cite
|
Sign up to set email alerts
|

Is a Technically Challenging Procedure More Likely to Fail? A Prospective Single-Center Study on the Short- and Long-Term Outcomes of Inguinal Hernia Repair

Abstract: Background and Aims The aim of this prospective single-center study was to evaluate the outcome of inguinal hernia repair. Materials and Methods A total of 485 inguinal hernias (452 patients and 33 patients with bilateral hernias) were operated between January 2004 and December 2010. Mean age was 56 years, and 93% were male. Patient demographics and operative data were collected, and the operating surgeon assessed the technical difficulty of the operation. Five years after surgery, a questionnaire evaluated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
1
6
0
2
Order By: Relevance
“…There are few studies assessing the predictors of pain after TEP repair. Onlay mesh placement, fixation of the mesh, strenuous physical activity, young age, and poor general health have been suggested to increase postoperative chronic pain incidence (11)(12)(13)(14). In our study, we found higher pain incidence with higher BMI, using microporous mesh, mesh fixation, fixation with titanium tacks, and at the beginning of the learning curve.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…There are few studies assessing the predictors of pain after TEP repair. Onlay mesh placement, fixation of the mesh, strenuous physical activity, young age, and poor general health have been suggested to increase postoperative chronic pain incidence (11)(12)(13)(14). In our study, we found higher pain incidence with higher BMI, using microporous mesh, mesh fixation, fixation with titanium tacks, and at the beginning of the learning curve.…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, postoperative chronic pain was 14% and 7.2% before and after the 50 th case (p=0.043). In a recent study, Berndsen et al (14) reported a 2.5% recurrence after 485 laparoscopic inguinal hernia repairs at a 5-year followup. Strenuous work (OR: 13.7), technically challenging repairs (OR: 7.2), and chronic discomfort (OR: 6.7) were the risk factors for recurrence in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Á Heilbrigðisstofnun Vesturlands á Akranesi hefur hins vegar verið starfraektur gagnagrunnur með öllum kviðslitsaðgerðum frá árinu 2004 og hafa niðurstöður úr 485 fyrstu nárakviðslitsaðgerðunum sýnt að árangur er vel sambaerilegur við það sem best gerist erlendis. 57 Til þess að haegt sé að hefja skráningu á árangri nárakviðslitsaðgerða hérlendis með miðlaegum gagnagrunni þarf þátttöku allra skurðlaekna sem framkvaema slíkar aðgerðir. Einnig er mikilvaegt að slíkur gagnagrunnur sé fjármagnaður af hinu opinbera þar sem utanumhald krefst mikillar vinnu.…”
Section: Langtíma áRangur Skurðaðgerðaunclassified
“…Inguinal hernias are common in the United States; with an approximated 800,000 inguinal hernia repairs performed each year [1] Inguinal hernias make up 75% of all abdominal wall hernias with two-thirds being indirect [1] , [2] . About 90% of all inguinal hernias occur in men with a broad age distribution [1] , [2] , [3] . Barring strangulated hernias, patients typically choose to wait and have an elective repair performed at a time of convenience [1] , [2] , [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%